تطبيقات نظرية علم لغة النص "دي بوجراند و دريسلر " على القران الكريم - Ayad Abdullah; Nur Azizi Ismail; Adnan Mohamed Yusoff (Centre of Quranic Research (CQR), University of Malaya, 2024)
Non-Indexed Publication